Atomic absorption spectrometry - Cantle, John Edward, 1949- (Techniques and instrumentation in analytical chemistry, 1982)
The topic is treated here in a very practical manner. The bulk of the book is concerned with real-life analyses for practising instrumentalists and differs from the literature supplied by manufacturers of atomic absorption instruments in that the methods described can be interpreted using all sorts of hardware, and in that far more chemistry and sample preparation are included.